(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Research on “Green Human Resource Management (GHRM)” has proliferated quickly in tandem with the increase in environmental awareness across the globe. According to research findings, firms that can integrate their HRM strategies with environmental management approaches reap both organizational and individual advantages. This research is the systematic analysis of empirical investigations on GHRM in the manufacturing sector. Using a systematically selected sample of 19 articles, we examined the theoretical underpinnings of the empirical research and the mediator, and moderator linkages between the antecedents and outcomes of GHRM in the manufacturing sector. We have also provided the platform for further research and additionally, this research looked into potential mediators and moderators that could be used in subsequent empirical GHRM investigations in the manufacturing sector.